PERKEMBANGAN EKONOMI HIJAU DI INDONESIA DALAM PERSPEKTIF GLOBAL: ANALISIS BIBLIOMETRIK DAN STRATEGI KEBIJAKAN - Prita Prasetya; Mochammad Mukti Ali (Juremi: Jurnal Riset Ekonomi, 2024)
The green economy is becoming an important focus of sustainability efforts and global economic strategies, influencing policy decisions, investment patterns, and technological innovations in various sectors. As more and more countries in the world are implementing green economy principles, the role of developing countries, such as Indonesia, is becoming increasingly significant. This study aims to conduct a bibliometric analysis of 195 journals indexed in the Scopus database to map the path of green economy research in Indonesia and juxtapose it with global trends. Using VOSviewer for visualization, the analysis identified key research themes that are influential in a comparative perspective on Indonesia's contribution to the global green economy. The study also identifies gaps in the literature, particularly in areas such as green finance, circular economy, and socio-economic implications of the transition to a green economy. Addressing these gaps through international interdisciplinary and collaborative research could enhance Indonesia's role in shaping the global green economy agenda